Religion and mental health among older adults: ethnic differences in Malaysia. (2nd November 2021) - Tan, Min Min; Su, Tin Tin; Ting, Rachel Sing-Kiat; Allotey, Pascale; Reidpath, Daniel
Abstract: Objectives: Religion and spirituality gain importance as a person ages. Research has shown that religion has a salutary effect on mental health, and it is associated with health differently across ethnic groups. The current study examined ethnic differences in the association between religion and mental health among older adults in a predominantly Muslim population and multicultural setting. Methods: Data of 7068 participants (4418 Malays, 2080 Chinese and 570 Indians) aged ≥55 years that were collected as part of the community health survey conducted in 2013 in the South East Asia Community Observatory (SEACO) were analyzed using bivariate and multiple regressions. Analyses were stratified by ethnicity. Results: The importance of having an enriched religious/spiritual life was associated with higher scores of depression, anxiety and stress among Chinese and higher score of depression among Malays, while belief in a higher power was associated with better mental health among Malays, Chinese and Indians. Conclusion: The current study showed that there were ethnic variations in the associations between religion and mental health, and the associations depended on the religious variable included in the analysis. The findings of this study showed that religion could be another potential channel to improve mental health among older adults by accommodating and understanding their religious beliefs.